Rancang Bangun Prototype Smart Home System Kontrol Lokal Area Menggunakan IoT MQTT Panel - Ilham Gunawan Mardianto; Aditya Chandra H; Widi Ariwibowo; Mahendra Widyartono (Jurnal Elektronika dan Teknik Informatika Terapan ( JENTIK ), 2023)
With the progress of civilization, science, and technology in Indonesia, the study entitled "Design and Development of Prototype Smart Home System using IoT MQTT Panel" aims to facilitate efficient control and monitoring of home activities. This smart home optimizes lighting, security, air, and garden systems, while saving electricity costs. The study adopts an experimental method to establish cause-effect relationships between factors by controlling other potential influences. Functional testing shows that the software system functions well and efficiently controls various aspects of the smart home. Failure value testing evaluates sensor performance, with the garden control showing the highest responsiveness at 93%. This indicates that the system provides a comprehensive solution for smart home management. Conclusion: Successful development of a smart home system using IoT MQTT Panel, effectively controlling lighting, air, security, and garden. Failure value testing shows an average sensor responsiveness of 90% and delay of 10.6%. Recommendations: Improve internet connectivity, add a camera, and conduct testing with different methods.